Crack in an anisotropic medium - Balueva, A.V.; Kuznetsov, S.V. (Archives of Mechanics, 1997)
A numerical method for the 3D problem of cracks in anisotropic media is developed, based on the variational approach to the crack opening problem. Properties of the pseudo-differential operator of the crack equilibrium problem are considered. Numerical examples are presented.